Ischemia-modified albumin levels as a biomarker of ischemic injury in dogs with parvoviral enteritis - Çakıral, E; Baydar, E; Karapınar, Z; Aydogdu, U (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to determine ischemia-modified albumin levels in dogs with parvoviral enteritis. The study was carried out on a total of 24 dogs, 16 with parvoviral enteritis (patient group) and 8 healthy (control group). The diagnosis of parvoviral enteritis was made by clinical findings, immunochromatographic rapid diagnostic kit, and PCR analysis of stool samples. For blood analysis, 3 ml of blood was taken from Vena cephalica antebrachi of dogs into tubes without anticoagulant before treatment, and the tubes were kept at room temperature for 30 minutes, then centrifuged at 5000 rpm for 5 minutes, serum samples were removed and the samples were stored at -20°C until analysis. While IMA, IMAO, and cTn I levels and capillary refill time were significantly higher in dogs with parvoviral enteritis than in healthy dogs (P<0.05), albumin levels were significantly lower (P<0.05). As a result, it was observed that cardiac damage developed in dogs with parvoviral enteritis and it would be useful to evaluate IMA and IMAO levels in the evaluation of ischemic damage.